Impact of anti-tubercular treatment on weight and symptoms of category I tuberculosis patients in an urban city of central India - Barnwal, Rajan K.; Gawande, Avinash V.; Narlawar, Uday W.; Zurmure, Sandip A. (International Journal Of Community Medicine And Public Health, 2020)
Background: Sputum conversion and weight gain are prognostic markers of treatment outcome in tuberculosis (TB) patients. Very few studies in India have assessed impact of TB treatment on weight of patients and perceived improvement in symptoms. This prospective study aimed to assess the impact of anti-tubercular treatment on weight and perceived symptoms. Methods: Three interviews were done for each patient i.e. at start (within 7 days of starting anti-tubercular treatment), at the end of intensive phase and at the end of continuation phase for recording body weight and perceived symptoms. Descriptive statistics were used to summarize baseline characteristics. Mean scores at different stages of treatment were compared by repeat measure ANOVA. P<0.05 was considered to be statistically significant. Results: Out of 58 study subjects enrolled for the study, 53 could be followed up till the end. Mean weight improved in six months of anti-tubercular treatment. Improvement was statistically non-significant. Cough and fever were the most common symptoms prior to beginning of treatment. After the first 2 months the proportion of subjects with symptoms declined for all five symptoms i.e. fever, cough, chest pain, sweats, and dyspnoea. Conclusions: There was positive impact on weight gain in patients under category I treatment. The symptoms improved drastically in first two months with near complete resolution in six months of treatment.